Active poly‐GA vaccination prevents microglia activation and motor deficits in a C9orf72 mouse model. Issue 2 (20th December 2019) - Zhou, Qihui; Mareljic, Nikola; Michaelsen, Meike; Parhizkar, Samira; Heindl, Steffanie; Nuscher, Brigitte; Farny, Daniel; Czuppa, Mareike; Schludi, Carina; Graf, Alexander; Krebs, Stefan; Blum, Helmut; et al.
Abstract: The C9orf72 repeat expansion is the most common genetic cause of amyotrophic lateral sclerosis (ALS) and/or frontotemporal dementia (FTD). Non‐canonical translation of the expanded repeat results in abundant poly‐GA inclusion pathology throughout the CNS. (GA)149 ‐CFP expression in mice triggers motor deficits and neuroinflammation. Since poly‐GA is transmitted between cells, we investigated the therapeutic potential of anti‐GA antibodies by vaccinating (GA)149 ‐CFP mice. To overcome poor immunogenicity, we compared the antibody response of multivalent ovalbumin‐(GA)10 conjugates and pre‐aggregated carrier‐free (GA)15 . Only ovalbumin‐(GA)10 immunization induced a strong anti‐GA response. The resulting antisera detected poly‐GA aggregates in cell culture and patient tissue. Ovalbumin‐(GA)10 immunization largely rescued the motor function in (GA)149 ‐CFP transgenic mice and reduced poly‐GA inclusions. Transcriptome analysis showed less neuroinflammation in ovalbumin‐(GA)10 ‐immunized poly‐GA mice, which was corroborated by semiquantitative and morphological analysis of microglia/macrophages. Moreover, cytoplasmic TDP‐43 mislocalization and levels of the neurofilament light chain in the CSF were reduced, suggesting neuroaxonal damage is reduced. Our data suggest that immunotherapy may be a viable primary prevention strategy for ALS/FTD in C9orf72 mutation carriers. Synopsis: The study proposes active immunization targeting poly‐GA as a prevention approach for pre‐symptomatic C9orf72 mutation carriers at risk of developping ALS/FTD. Immunization using Ovalbumin‐(GA)10 largely rescued motor deficits in a poly‐GA mouse model. Ovalbumin‐(GA)10 immunization drives strong anti‐GA response without apparent side effects. Ovalbumin‐(GA)10 immunization reduces motor deficits and poly‐GA inclusions. Ovalbumin‐(GA)10 immunization attenuates neuroinflammation, neuroaxonal damage and reduces cytoplasmic TDP‐43 mislocalization. Abstract : The study proposes active immunization targeting poly‐GA as a prevention approach for pre‐symptomatic C9orf72 mutation carriers at risk of developping ALS/FTD. Immunization using Ovalbumin‐(GA)10 largely rescued motor deficits in a poly‐GA mouse model.